Lipid Association of India (LAI) expert consensus statement on management of dyslipidaemia in Indians 2017: part 2. (1st January 2017) - Iyengar, S. S.; Puri, R.; Narasingan, S. N.; Nair, D. R.; Mehta, V.; Mohan, J. C.; Wangnoo, S. K.; Dalal, J. J.; Jha, V.; Puri, S.; Misra, A.; Daga, M. K.; et al.
ABSTRACT: These Lipid Association of India (LAI) recommendations refer to specific patient populations. They follow the previously published LAI part 1 recommendations. These part 2 LAI recommendations focus on specific patient groups. These include patients with heart failure, chronic kidney disease, non-alcoholic fatty liver disease, cerebrovascular disease, thyroid disorders, inflammatory joint diseases, familial hypercholesterolaemia and human immunodeficiency virus infection. We also consider women, the elderly and post-transplantation patients. The current recommendations are based, as much as possible, on available data from Indian populations.